Counting with Colours? Effect of Colours on the Numerical Abilities of House Crows (Corvus splendens) and Common Myna (Acridotheres tristis) - Nor Amira Abdul Rahman; Zalila Ali; Wan Fatma Zuharah; Nik Fadzly (Tropical Life Sciences Research, 2016)
We conducted several aviary experiments to investigate the influence of colours in quantity judgments of two species of birds; house crow (Corvus splendens) and common myna (Acridotheres tristis). Different quantity (in seven different food proportions) of mealworms were presented nonsequentially to all birds using artificially coloured red mealworms, for experiment 1, and using artificially coloured green mealworms, for 2 experiment 2. Both red and green coloured mealworms have no significant effect on house crow’s quantity judgments (red: ANOVA: F?‚?? = 1.748, p = 0.144; and green: ANOVA: F?‚?? = 1.085, p = 0.394). Common myna, however, showed a strong influence of red colour in their quantity judgment (ANOVA: F?‚?? = 2.922, p = 0.023) as they succeeded in choosing the largest amount of food between two cups, but not when offered food using green coloured mealworms (ANOVA: F?‚?? = 1.183, p = 0.342). In the next experiment, we hypothesised that both house crow and common myna will prefer red coloured food items over green coloured food items, when factors such as the amount of food is equal. We chose to test red and green colours because both colours play an important role in most avian food selections. Results showed that there were no significant differences in the selection of red or green coloured mealworms for both house crows (ANOVA: F?‚?? = 2.310, p = 0.06) and common myna (ANOVA: F?‚?? = 0.823, p = 0.561). Kami menjalankan beberapa eksperimen aviari untuk mengenal pasti kesan warna ke atas pemilihan kuantiti oleh dua jenis burung, burung gagak (Corvus splendens) dan burung tiung (Acridotheres tristis). Cacing dalam kuantiti berbeza (tujuh pembahagian berlainan) diberikan kepada burung dalam turutan rawak menggunakan cacing dicat dengan warna merah bagi eksperimen 1 dan menggunakan cacing dicat warna hijau bagi eksperimen 2. Kedua-dua warna cacing merah dan hijau tidak memberi kesan kepada pemilihan kuantiti gagak (merah: ANOVA: F?‚?? = 1.748, p = 0.144; dan hijau: ANOVA: F?‚?? = 1.085, p = 0.394). Namun demikian, burung tiung menunjukkan kesan pengaruh kuat bagi warna merah ke atas pemilihan kuantiti (ANOVA: F?‚?? = 2.922, p = 0.023), dengan burung berjaya memilih jumlah makanan yang lebih besar antara dua cawan, tetapi tidak apabila cacing berwarna hijau ditawarkan (ANOVA: F?‚?? = 1.183, p = 0.342). Dalam eksperimen seterusnya, hipotesis kami ialah kedua-dua burung gagak dan burung tiung akan memilih makanan berwarna merah berbanding warna hijau apabila faktor jumlah makanan adalah sama. Kami memilih untuk menguji warna merah dan warna hijau kerana kedua-dua warna memainkan peranan penting dalam pemilihan makanan burung. Keputusan menunjukkan tiada perbezaan signifikan bagi pemilihan cacing merah dan hijau bagi kedua-dua burung gagak (ANOVA: F?‚?? = 2.310, p = 0.06) dan burung tiung (ANOVA: F?‚?? = 0.823, p = 0.561).